Pengaruh Likuiditas dan Ukuran Perusahaan Terhadap Agretivitas Pajak Perusahaan - Hanafairus, Lisita; Khasanah, Uswatun; Nuryati, Tutty (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The analysis of the theory behind tax planning, deferred tax liabilities, and current tax burden on earnings management is the goal of this study. A quantitative strategy combined with a literature review method is used in this investigation. The theoretical underpinnings, additional explanatory factors, and research findings from earlier literature are presented in this study. Positive accounting theory is the foundation of this study. Liquidity and corporate size are supporting factors that affect aggression. These findings demonstrate a significant relationship between business size and aggressiveness that helps to reduce current expenditures. The occurrences that occur are described in further detail in this paper.